Labor supply and demographics: A case of Pakistan. (13th March 2019) - Kanwal, Warisha; Rizwan Ahmad, Hafiz; Arshed, Noman; Gulzar, Muhammad
Abstract : Generally, the labor supply curve oversimplifies the dynamics behind the decision to work. This study is aimed at finding out the cross‐section‐based determinants of total working hours in Pakistan. The analysis is carried out by using microdata from Labor Force Survey (2010–2011). The data showed that there is a significant share of people who are working for less than 35 hours a week, between 35 and 48 hours a week, and more than 48 hours a week. There is a need to explore the determinants of work hours, because in Pakistan there are 11.9% people who are underemployed and 40.2% people who are overemployed. The econometric analyses described the determinants of total working hours by personal factors (age, gender, education, and marital status), household characteristics (household size and number of siblings), and regional characteristics (such as province and region). For this purpose, the study uses linear regression analysis. Moreover, one of the main contributions of the study is that empirical studies fail to show due interest in depicting the severity of excessive utilization of human capital for a developing country like Pakistan. The present study fills this gap by presenting a detailed descriptive and econometric analysis of total working hours.